Diversity and useful products in some Verbenaceous member of Melghat and Amravati regions, Maharashtra, India - SHUBHANGI NAGORAO INGOLE (Biodiversitas Journal of Biological Diversity, 2011)
Ingole SN. 2011. Diversity and useful products in some Verbenaceous member of Melghat and Amravati regions, Maharashtra, India. Biodiversitas 12: 146-163. Verbenaceae is a large family of very diverse habit. The present study deals with detailed characteristics, distribution and economically important products of some verbenaceous members of Melghat and Amravati regions. During the survey twenty members belonging to fourteen genera of Verbenaceae were collected. Some members occur abundantly either in wild or cultivated state like Lantana camara L. var. aculeata Mold., Lantana flava Medik., L. nivea Vent., Glandularia bipinnatifida (Schauer)Nutt., Duranta erecta L., Vitex negundo L., Volkameria inermis L., Clerodendrum phlomidis L. f., Clerodendrum splendens G. Don, Nyctanthes arbor-tristis L. etc. while Petrea volubilis L., Gmelina arborea Roxb., G. philippensis Cham., Stachytarpheta jamaicensis (L.) Vahl., S. mutabilis (Jacq.) Vahl., Rotheca serrata (L.) Steane & Mabb., Holmskioldia sanguinea Retz. are not much common and occur in limited locations. Phyla nodiflora (L.) Greene, a creeping much-branched herb is found typically in wet places. Tectona grandis L. f. occurs very variable in size according to its habitat and is common dominant tree in forest of Melghat and also planted in plains. Clerodendrum infortunatum L., a gregarious tomentose shrub is exclusively found in shades of forest at limited spots in higher elevations of Melghat. The various members are not only beautiful ornamentals but also the source of important medicinal products useful in a broad range of diseases including skin disorders and snake remedies; they contain alkaloids, sterols, saponin, glucosides, dyes etc. and are economically quite important e.g. as high quality timber. On basis of morphological diversity the generic key is provided.